2018
DOI: 10.3389/fimmu.2018.02640
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viral Infection-Induced Microbiome Alterations and Secondary Bacterial Pneumonia

Abstract: Influenza and other respiratory viral infections are the most common type of acute respiratory infection. Viral infections predispose patients to secondary bacterial infections, which often have a more severe clinical course. The mechanisms underlying post-viral bacterial infections are complex, and include multifactorial processes mediated by interactions between viruses, bacteria, and the host immune system. Studies over the past 15 years have demonstrated that unique microbial communities reside on the muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
357
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(369 citation statements)
references
References 145 publications
7
357
0
5
Order By: Relevance
“…Aside from the pathogen, microbiota in the lung is associated with disease susceptibility and severity [7]. Alterations of lung microbiota could potentially modify immune response against the viral and secondary bacterial infection [8,9]. Thus, understanding the microbiota, which comprises bacteria that could cause secondary infection or exert effects on the mucosal immune system, might help to predict the outcome and reduce complications.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the pathogen, microbiota in the lung is associated with disease susceptibility and severity [7]. Alterations of lung microbiota could potentially modify immune response against the viral and secondary bacterial infection [8,9]. Thus, understanding the microbiota, which comprises bacteria that could cause secondary infection or exert effects on the mucosal immune system, might help to predict the outcome and reduce complications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results of multiplex PCR must be interpreted together with the patients' clinical presentation. However, there is also evidence suggesting that subclinical viral infection leads to alteration of the host-microbe composition of the respiratory tract, which might be linked to subsequent dysregulation in host immune function associated with development of asthma or against bacterial infection [23,24]. The impact of altered microbiota in the respiratory tract after viral infections awaits future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated that respiratory infections are associated with a change in the composition of the gut microbiota (Wang et al, 2014;Deriu et al, 2016;Bartley et al, 2017;Groves et al, 2018;Hanada et al, 2018;Yildiz et al, 2018). We have previously observed that viral lung infections alter the gut microbiota, leading to an increase in the relative abundance of Bacteroidetes and a decrease in the relative abundance of Firmicutes (Groves et al, 2018).…”
Section: Introductionmentioning
confidence: 97%